Depression in Patients with Cardiovascular Disease. (5th July 2012) - Mastrogiannis, Dimos; Giamouzis, Gregory; Dardiotis, Efthimios; Karayannis, George; Chroub-Papavaiou, Artemis; Kremeti, Dimitra; Spiliopoulos, Kyriakos; Georgoulias, Panagiotis; Koutsias, Stelios; Bonotis, Konstantinos; Mantzorou, Marianna; Skoularigis, John; et al.
Abstract : It has been widely suggested that depression negatively affects patients with cardiovascular disease. There are several pathophysiological mechanisms as well as behavioral processes linking depression and cardiac events. Improvements in nursing and medical care have prolonged survival of this patient population; however, this beneficial outcome has led to increased prevalence of depression. Since mortality rates in chronic heart failure patients remain extremely high, it might be as equally important to screen for depression and there are several valid and reliable screening tools that healthcare personnel could easily employ to identify patients at greater risk. Consultation should be provided by a multidisciplinary team, consisting of cardiologists, psychiatrists, and hospital or community nurses so as to carefully plan, execute, and evaluate medical intervention and implement lifestyle changes. We aim to systematically review the existing knowledge regarding current definitions, prognostic implications, pathophysiological mechanisms, and current and future treatment options in patients with depression and cardiovascular disease, specifically those with heart failure.